2002
DOI: 10.1080/0042098022000033854
|View full text |Cite
|
Sign up to set email alerts
|

Urban Economic Growth in China: Theory and Evidence

Abstract: This paper analyses the relationship between per capita GDP growth and investment, foreign direct investment, labour force growth, government expenditure and urban infrastructure based on the data for 189 large and medium-sized Chinese cities for the period of 1991-98. Cross-sectional analyses indicate that several factors, such as foreign investment, paved roads and government expenditure on science and technology are positively related to per capita GDP growth, while the overall size of government, measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 34 publications
4
17
1
Order By: Relevance
“…Meanwhile, Lin and Song (2002) study the relationship between per capita GDP growth and investment, foreign direct investment, employment growth, government budget and infrastructure for large and medium sized cities in China from 1991 to 1998. Cross-sectional analysis shows that foreign investment, infrastructure, and government spendings for science and technology have positive relationship with per capita GDP growth, while other government budget as a whole have a negative impact on growth of GDP per capita.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, Lin and Song (2002) study the relationship between per capita GDP growth and investment, foreign direct investment, employment growth, government budget and infrastructure for large and medium sized cities in China from 1991 to 1998. Cross-sectional analysis shows that foreign investment, infrastructure, and government spendings for science and technology have positive relationship with per capita GDP growth, while other government budget as a whole have a negative impact on growth of GDP per capita.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A great deal of emphasis has been placed on the role of foreign direct investment (FDI), which is believed to be more productive than domestic investment because it introduces new technologies and new production methods that enhance human capital and because it induces host governments to make additional investments in infrastructure (Zhang and Zhou, 1998; Lin and Liu, 2001; Fujita and Hu, 2001; Zhang, 2001; Gao, 2003). Other studies have demonstrated the importance of investments in physical and institutional infrastructure and services provided by government (Démurger, 2001; Lin and Song, 2002).…”
Section: Previous Literaturementioning
confidence: 99%
“…A time‐series analysis of urbanization levels in China over the period 1978–2000 conducted by Zhang (2002) attributes urban growth to economic growth generally, increases in employment opportunities in manufacturing and services, and FDI. A cross‐section analysis of urban growth rates conducted by Lin and Song (2002) finds evidence that FDI, infrastructure investment, and investment in human capital contributed to per capita GDP growth in 189 Chinese cities over the period 1991–1998 while the effects of domestic investment and population growth were, if anything, negative. Anderson and Ge (2004) obtained similar results from a cross‐section analysis comparing urban growth rates in 220 Chinese cities during the period 1990–1999.…”
Section: Previous Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Akitoby et al (2006) argue that, though there is strong evidence from industrialized countries, Wagner"s law does not hold true in developing countries like China. Recent studies also cast doubt on the existence of Wagner"s law (Halicioglu 2003;Lin and Song, 2002;Iyare and Lorde, 2004;Ram 1987;Sinha 2007;Zhang 2007Zhang , 2008aZiramba 2008). The existing studies usually fail to address the endogeneity issue when they test the validity of Wagner"s law.…”
Section: Variables Explaining Government Size and Theoretical Argumentsmentioning
confidence: 99%